PENGARUH KOMPENSASI FINANSIAL, SEMANGAT KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN PENGOLAHAN PT. PERINDUSTRIAN DAN PERDAGANGAN BANGKINANG - Nanda Pranata; Machasin -; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine how the effects of financial compensation variable, Spirit of Worked and working environment simultaneously and partially on employee job satisfaction processing section PT. Industry and Trade Bangkinang. In this study, the study population were employees of the processing Pt. Industry and Trade Bangkinang totaling 104 people. The sampling method used was convenience sampling, which means sampling was done by members of the population were met by chance and were willing to become respondents. Analysis of the data used was descriptive analysis and quantitative analysis of multiple linear regression with SPSS for Windows version 18.00. From the results of the testing that has been done, simultaneous regersi test (Test-F) shows that financial compensation, spirit of work and working environment simultas effect on job satisfaction. The result of partial test (t-test) showed that financial compensation variable, spirit of work and working environment significantly influence job satisfaction.Keywords: Compensation, Spirit of Work and Work Environment On The Processing of Employee Satisfaction